Wyman Ford : The Kraken Project - Book 4 - Preston, Douglas J (New York : Forge, 2014)
"NASA's Goddard Space Flight Center is designing a probe which will be dropped into the Kraken Mare, one of the methane seas of Titan. There, it will embark on a journey of exploration. As the probe is being tested at Goddard, things go awry, and an explosion kills seven scientists. The AI program in the probe, a powerful, self-modifying AI called "Dorothy," flees into the Internet. Series character Wyman Ford is tapped by the president's science advisor to track down the software with the help of Dorothy's creator, Melissa Shepherd. As the two of them trace Dorothy in her wanderings in cyberspace, they realize Dorothy's horrific experiences in the wasteland of the Internet have changed her--utterly. But for the better . . . or worse? At the same time, they learn Dorothy is being pursued by a pair of Wall Street high-frequency traders, who want to turn her into an algorithmic-trading slave-bot. Pursued relentlessly by the traders, Dorothy jumps out of the Internet into a child's toy robot, to hide. Now the only person standing between the murderous algo traders and Dorothy is a lonely, twelve-year-old boy living on an isolated bay on the coast of northern California. But is Dorothy bent on doing good . . . or on wiping out the cancer of the human race?"--
"A Tom Doherty Associates book."
Booklist
Library Journal
Publishers Weekly
Kirkus Reviews
Adult.
Keywords: Artificial intelligence -- Fiction; Cyberspace -- Fiction; Adventure fiction; Science fiction